1996
DOI: 10.1029/95jc03796
|View full text |Cite
|
Sign up to set email alerts
|

Air‐sea exchange of water vapor and sensible heat: The Humidity Exchange Over the Sea (HEXOS) results

Abstract: Abstract. Surface layer fluxes of sensible heat and water vapor were measured from a fixed platform in the North Sea during the Humidity Exchange over the Sea (HEXOS) Main Experiment (HEXMAX). Eddy wind stress and other relevant atmospheric and oceanic parameters were measured simultaneously and are used to interpret the heat and water vapor flux results. One of the main goals of the HEXOS program was to find accurate empirical heat and water vapor flux parameterization formulas for high wind conditions over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
184
1
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 238 publications
(202 citation statements)
references
References 67 publications
15
184
1
2
Order By: Relevance
“…Andreas (2004) by Sahlée et al (2007), showed that the expected contribution of spray to the flux of sensible heat in this wind speed range is only 5-10%. This finding is also in general agreement with the conclusions from the HEXOS experiment, Decosmo et al (1996); cf. also Andreas and DeCosmo (2002).…”
Section: Introductionsupporting
confidence: 82%
“…Andreas (2004) by Sahlée et al (2007), showed that the expected contribution of spray to the flux of sensible heat in this wind speed range is only 5-10%. This finding is also in general agreement with the conclusions from the HEXOS experiment, Decosmo et al (1996); cf. also Andreas and DeCosmo (2002).…”
Section: Introductionsupporting
confidence: 82%
“…It was found that the often used bulk transfer coefficients for sensible heat of Large and Pond (1982) or of Smith (1988) lead to a considerable underestimation of sensible heat fluxes under the conditions experienced over the Labrador Sea in winter, that is, large air-sea temperature differences and high wind speeds. Parameterizations according to Isemer and Hasse (1987), Anderson and Smith (1981), DeCosmo et al (1996), and Anderson (1993) give reasonable results for an area like the Labrador Sea during wintertime.…”
Section: Discussionmentioning
confidence: 98%
“…Compared with dissipation sensible heat fluxes, the Bunker parameterization overestimates fluxes by 13%. Parameterizations according to Anderson and Smith (1981), DeCosmo et al (1996), and Anderson (1993) underestimate the measured fluxes by approximately 10%; those of Large and Pond (1982) and Smith (1988) underestimate sensible heat fluxes by more than 18% and 34% compared to estimates based on the inertial dissipation method.…”
Section: Sensible Heat Fluxmentioning
confidence: 99%
See 2 more Smart Citations